217k views
3 votes
Chris tried to rewrite the expression \left( 4^{-2} \cdot 4^{-3} \right)^{3}(4 −2 ⋅4 −3 ) 3 left parenthesis, 4, start superscript, minus, 2, end superscript, dot, 4, start superscript, minus, 3, end superscript, right parenthesis, cubed. \begin{aligned} &\phantom{=}\left( 4^{-2} \cdot 4^{-3} \right)^{3} \\\\ &=\left( 4^{-5} \right)^{3}&\text{Step } 1 \\\\ &=4^{-2}&\text{Step } 2 \\\\ &=\dfrac{1}{4^{2}}&\text{Step } 3 \end{aligned} ​ =(4 −2 ⋅4 −3 ) 3 =(4 −5 ) 3 =4 −2 = 4 2 1 ​ ​ Step 1 Step 2 Step 3 ​ Did Chris make a mistake? If so, in which step? Choose 1 answer: Choose 1 answer: (Choice A) A Chris did not make a mistake. (Choice B) B Chris made a mistake in Step 1. (Choice C) C Chris made a mistake in Step 2. (Choice D) D Chris made a mistake in Step 3.

2 Answers

4 votes

Answer:

Chris made a mistake in step 2.

Explanation:

I was solving this problem just now and I searched it up here. Now I got the answer :)

User Mike Yockey
by
5.0k points
0 votes

Answer: Chris made a mistake in step 2

(It was in Khan Academy)

User Yogesh Wadhwa
by
4.4k points